The Use of Hydraulic Fracturing in Stimulation of the Oil and Gas Wells in Romania - Pană, Ion; Gheţiu, Iuliana Veronica; Stan, Ioana Gabriela; Dinu, Florinel; Brănoiu, Gheorghe; Suditu, Silvian (Sustainability, 2022)
This paper presents the application of the hydraulic fracturing method in Romania, exemplified by three case studies. In the current conditions in which the oil and gas prices have risen above the limit of affordability, Romania, one of the few producers in Europe, is trying to solve the problems that have arisen through various methods, which are as follows: offshore drilling, gas underground storage, field rehabilitation and increasing the efficiency of applied technologies. The application of hydraulic fracturing is a safe process, with minimal environmental implications and certain economic benefits. The important thing is to have the necessary energy now, in the desired quantities and with minimal expenses. The authors sought to include key issues in the application of this technology in Romania. The scientific literature on this topic has helped us to interpret the data from the field in difficult situations and were a real support in our activity. We need to provide energy support and energy security and we do not have a lot of resources. Under these conditions, the reactivation of existing deposits and the extension of the production period are essential elements. The authors designed the fracturing technologies. The data corresponding to the geological structure obtained through geological investigations, and the database corresponding to the analyzed wells from the company’s data archive were the elements used in the simulation programs. Thus, the values in the fracturing area about pore fluid permeability, layers stress, Young’s modulus of the structure and fracture toughness were established. The fluids for the fracturing operation and the proppant were chosen for each case, in accordance with the geological recommendations, by our team. Testing of the fracturing technologies for different variants of the pumping program was carried out using the Fracpro program. The variants presented in this article are some of the best solutions found. We used the step-by-step flow test to find the fracture expansion pressure and closing pressure for each case. The mini-frac program established corrections to the designed technologies during the operation quickly and with reduced costs. The designed technologies allowed us to anticipate the necessary flows and pressure, leading to the choice of equipment. The fracture operations were performed only after the projected technologies anticipated the economic benefits covering the investments for the use of the equipment and the operation itself. Knowing the measured pressure of the well and the conditions of communication with the gas/oil reservoir, a simulation of the gas/oil production that could be obtained was made with the simulator. Two situations were exemplified for a gas well and an oil well. The field production results for a two-year interval are also indicated for these wells and a comparison was made with the estimated production.